Religious Appreciation as a Predictor of Psychological Well-being in Malaysian Educational Settings - Sapiee, Mohd Lokman; Abdullah, Ismail Naim; Jamaludin, Mohd Syarifuddin; Zabidi, Mohamad Irfan Mohamad; Romil, Muhammad Rozaidi Ahmad; Ibrahim, Nurshahira (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the relationship between religious appreciation and psychological well-being among Malaysian secondary school students. Within Malaysia's unique multi religious context, understanding how religious appreciation influences adolescent psychological development has significant implications for educational policy and practice. Using a cross-sectional research design, data were collected from 290 secondary school students across three institutions in Perak, Malaysia, predominantly comprising Malay students (99.3%) aged 13-16 years. Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed religious appreciation significantly predicted psychological well-being (β = 0.391, t = 7.682, p < 0.001) with a moderate effect size (f² = 0.180), explaining 15.3% of variance in psychological well-being. Measurement model assessment confirmed satisfactory reliability and validity for both constructs. These findings demonstrate that religious appreciation constitutes a meaningful contributor to adolescent psychological well-being in Malaysia's educational context, suggesting that nurturing religious understanding and appreciation may support positive psychological development among secondary school students, regardless of their specific faith tradition.